Toward evidence-based prescription of prosthetic ankle-foot devices: A multisite randomized crossover trial identifying performance-based, patient-reported, and biomechanical parameters sensitive to device type - Jason T. Maikos; Alexis N. Sidiropoulos; John M. Chomack; David V. Herlihy; Brad D. Hendershot; Alison L. Pruziner; Samuel L. Phillips; Jeffrey T. Heckman; Timothy E. Moore; Zoe Gibbs McBride; Jongwoo Choi; Christopher L. Dearth; et al. (PLoS ONE, 2026)
Prescription of prosthetic ankle-foot devices is constrained by imprecise clinical guidelines and inconsistent scientific evidence, hindering optimal device selection for individuals with lower limb loss. This multisite, prospective, randomized crossover study aimed to identify patient-reported, performance-based, and biomechanical parameters sensitive to ankle-foot device type, providing a foundation for more objective and individualized prescription practices. Ninety-one individuals with unilateral transtibial limb loss completed the crossover trial, and 13 control participants without musculoskeletal impairment were enrolled to provide normative reference data. Participants were fitted with duplicate sockets and randomized to trial three ankle-foot device types: energy storing and returning, articulating, and powered. Participants were heterogeneous in demographic characteristics, including veterans, service members, and civilians. After one week of acclimation per device, participants completed performance-based (6-minute walk, Timed Up and Go, Four Square Step Test, Stair and Hill Assessment Indices, Amputee Mobility Predictor) and patient-reported (Prosthesis Evaluation Questionnaire, 12-Item Short Form Health Survey, Orthotics and Prosthetics Users’ Survey) assessments; a subset (n = 29 completed) underwent full-body gait analysis to capture detailed biomechanical parameters. Biomechanical outcomes demonstrated the greatest sensitivity to device type, with 19 distinct parameters, primarily at the ankle, highlighting ankle mechanics as a key determinant of differences among prosthetic devices. Five Prosthesis Evaluation Questionnaire subscales were sensitive to device type, while performance-based measures showed no significant effects. Results revealed a dichotomy between biomechanical and patient-reported outcomes: Biomechanical parameters were more similar to control values for powered devices, whereas patient-reported outcomes favored non-powered devices. Linear discriminant analysis identified key gait features, including peak plantarflexion during preswing and peak ankle moment, which most strongly contributed to group separation and clinical discrimination. These findings identified distinct biomechanical and patient-reported parameters sensitive to ankle-foot device type and highlight the need for evidence-based, individualized prosthetic prescription to optimize device selection and improve patient outcomes.